2000
DOI: 10.1063/1.126870
|View full text |Cite
|
Sign up to set email alerts
|

Cd–Ne direct current glow discharge: An efficient source of ultraviolet radiation

Abstract: This investigation aims to present data of a potential light source based on Cd. Recent study of cadmium–neon direct current glow discharge at low and intermediate pressure showed that a significant fraction (∼80%) of the input power delivered to the plasma can be converted into resonance radiation, which leads us to conclusion that Cd can be an efficient light source, even more efficient than Hg. The conventional fluorescent lamps contain Hg, but environmental concerns urge for mercury-free light sources. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Most of the absorbance spectra in that region are perturbed by noise; however, in some cases, some optical absorption peaks are observed, which could be related with these PL bands. These emissions seem to be the intraatomic energy transitions of the Cd atom: (a) 5p 3 P 0 , (b) 5p 3 P 1 , and (c) 5p 3 P 2 to 5s 1 S 0 , with energy transitions 3.74, 3.80, and 3.95 eV, respectively [71]; these values have an average value of 0.06 eV. Then, the emissions reported in this work come from Cd atoms transitions.…”
Section: (Right)mentioning
confidence: 98%
“…Most of the absorbance spectra in that region are perturbed by noise; however, in some cases, some optical absorption peaks are observed, which could be related with these PL bands. These emissions seem to be the intraatomic energy transitions of the Cd atom: (a) 5p 3 P 0 , (b) 5p 3 P 1 , and (c) 5p 3 P 2 to 5s 1 S 0 , with energy transitions 3.74, 3.80, and 3.95 eV, respectively [71]; these values have an average value of 0.06 eV. Then, the emissions reported in this work come from Cd atoms transitions.…”
Section: (Right)mentioning
confidence: 98%
“…An obvious way of designing alternative fluorescent lamps involves the replacement of mercury with other metals of the same element group, which also show an efficient UV emission. In studies of a neon-cadmium dc column plasma an efficiency of about 80% has been reported for the 223 and 326 nm resonance radiation of Cd [2]. Here, a total pressure of 200 Pa, currents in the range from 100 to 300 mA in a tube of 30 mm in diameter and an admixture of 5% Cd have been applied.…”
Section: Introductionmentioning
confidence: 99%